Desnutrición y anemia, en preescolares que acuden al Centro de Salud No. 1 - Jara Carreño, Tatiana del Carmen (2016)
Malnutrition remains one of the most serious public health problems affecting children under the age of 5 years old within Ecuador. The highest percentage of malnutrition is found in rural areas with 26%; this problem is exacerbated by anemia, which in most cases can be prevented. Based on the aforementioned, an analytical, observational and prospective study was carried out to achieve the following objectives: first, identify which preschoolers treated at health center No. 1 presented malnutrition; second, identify which preschoolers treated at health center No. 1 presented anemia; third, demonstrate the relationship between anemia and malnutrition in preschoolers treated at health center No. 1. The study population comprised 473 children, and the sample consisted of 101 children who met the criteria for inclusion and exclusion. The results determined that 24.5% presented malnutrition and anemia; of which, 95.05% had mild malnutrition and 93.07% had mild anemia, concluding that 100% of malnourished children had anemia. Keywords: malnutrition, anemia and preschoolers.